A systematic review and meta-analysis of acupuncture's impact on hemiplegic gait recovery after stroke - Zheng Sun; Haitian Sun; Kuang Yu; Zilong Zhu; Yiren Lin; Ke Sun; Jianbin Zhang (Complementary Therapies in Medicine)
Objective: This systematic review aims to evaluate the efficacy and safety of acupuncture in alleviating gait disturbances in post-stroke hemiplegia, focusing on various gait parameters. Methods: A comprehensive search was conducted across PubMed, EMBASE, Cochrane Library, Web of Science, AMED, CINAHL, CBM, CNKI, and WanFang databases to identify relevant randomized controlled trials (RCTs). The included studies were independently evaluated for risk of bias using Cochrane's risk of bias tool. RevMan 5.3 was used for meta-analysis, and adverse events were collected through full-text review. Results: A total of 21 RCTs involving 1463 participants were included. Results showed that acupuncture combined with rehabilitation therapy (RT) significantly improved stride and step length (MD = 7.79, 95 % CI: 5.62–9.96, Z = 7.03, P < 0.00001, I² = 72 %), cadence (MD = 10.43, 95 % CI: 6.22–14.65, Z = 4.85, P < 0.00001, I² = 95 %), walking speed (MD = 12.27, 95 % CI: 9.22–15.31, Z = 7.90, P < 0.00001, I² = 91 %), hip peak flexion angle (MD = 2.71, 95 % CI: 0.94–4.49, Z = 2.99, P = 0.003, I² = 82 %), and ankle peak plantarflexion angle (MD = 2.08, 95 % CI: 1.11–3.06, Z = 4.19, P < 0.0001, I² = 0 %) compared to RT alone. It also reduced gait cycle time (MD = −0.61, 95 % CI: −0.96 to −0.26, Z = 3.44, P = 0.0006, I² = 98 %) and the proportion of double support phase (MD = −7.16, 95 % CI: −9.08 to −5.25, Z = 7.33, P < 0.00001, I² = 0 %). These improvements in gait parameters suggest enhanced mobility and functional independence for post-stroke patients. However, heterogeneity in participant characteristics and study methodologies was noted, such as variations in stroke types, curses, severity, and acupuncture protocols. The majority of RCTs exhibited moderate to high risk of bias regarding allocation concealment and blinding. Only two RCTs reported no adverse events, while the rest 19 studies did not mention adverse events. Conclusion: Acupuncture appears to enhance specific aspects of hemiplegic gait, though further high-quality research is needed to fully validate its effects. Current evidence is limited by methodological weaknesses and potential biases in the included studies. Rigorous, well designed studies are needed to further validate the comprehensive effects of acupuncture on post-stroke hemiplegic gait.